Approach and avoidant coping: Implications for adolescent mental health - Herman-Stahl, Mindy A.; Stemmler, Mark; Petersen, Anne C. (Journal of Youth and Adolescence, 1995)
Conducted a short-term longitudinal study examining the structure of coping behavior and the relationship between coping style and depression during adolescence. 603 adolescents in Grades 6–11 were surveyed in the fall of 1989 and again in the fall of 1990. A 2-dimensional model of coping was found using confirmatory factor analysis, with the factors being approach coping and avoidant coping. Approach copers reported the fewest symptoms of depression, while avoidant copers reported the most. Girls used more approach coping than did boys in all grades. Ss who changed over time from approach to avoidant coping evidenced a significant increase in depressive symptoms, whereas Ss who switched from avoidant to approach coping displayed a significant decrease in depression over 1 yr.
Keywords: Coping Behavior; Major Depression; Longitudinal Studies